Basics of Neurointervention - Matin, Tariq; Deshmukh, Aviraj; Al-Schameri, A. R. (Indian Journal of Neurosurgery, 2018)
Neurointervention is a subspecialty of neurosciences which offers a minimally invasive therapy for the vascular lesions of the central nervous system. The resources, techniques, and indications of neurointervention therapy are rapidly expanding and becoming diverse. With the support of robust scientific data, neurointervention has established itself as a first line therapy for many neurovascular diseases. This article provides an overview about the various material used in neurointervention, basic steps followed in some common neurointerventional procedures, and its related complications. In the era of 21st century, any young physician or surgeon as well as residents-in-training dealing with neurovascular cases should have some insight into these basic concepts so as to provide better care to their patients.
Keywords: neurointervention; catheter; wires